2021
DOI: 10.1007/s12070-021-02702-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Olfactory and Gustatory Dysfunction in Coronavirus Disease (COVID-19): A Cross Sectional Study in Our Tertiary Care Hospital

Abstract: COVID-19 pandemic is affecting millions of people all across the globe. Along with other clinical features, anosmia and dysgeusia are important symptoms being seen. This study evaluates the prevalence of olfactory and gustatory dysfunction in patients with SARS CoV-2 infection in a tertiary care centre and the severity and duration of altered taste and smell sensation in COVID positive patients. A total number of 167 patients that had tested positive for COVID 19 KLES Dr. Prabhakar Kore hospital in the study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…These 40 studies (reporting on 43 cohorts) were subjected to a meta-analysis (Table ). Fifteen studies reported anosmia prevalence in 18 cohorts with a total of 7247 COVID-19 patients from regions where the D614 virus was dominant: three studies from Kuwait or Singapore and 12 from India or Pakistan. We compared such data with the results obtained in 25 studies reporting on 25 cohorts with a total of 9626 South Asian patients from the Indian subcontinent (India and Bangladesh) and Oman, when the G614 virus had become dominant (Table , illustrated in Figure A and B). , The differences in results between the two types of cohorts are shown in the forest plots (Figure A). The pooled prevalence of olfactory dysfunction in the same ethnicity (South Asians) in regions with D614 predominance was 5.33% (95% confidence interval, CI = 3.52–8.00%), while in regions with G614 predominance, it was 31.79% (95% CI = 23.26–41.76%) (Figure A, C).…”
Section: Resultsmentioning
confidence: 99%
“…These 40 studies (reporting on 43 cohorts) were subjected to a meta-analysis (Table ). Fifteen studies reported anosmia prevalence in 18 cohorts with a total of 7247 COVID-19 patients from regions where the D614 virus was dominant: three studies from Kuwait or Singapore and 12 from India or Pakistan. We compared such data with the results obtained in 25 studies reporting on 25 cohorts with a total of 9626 South Asian patients from the Indian subcontinent (India and Bangladesh) and Oman, when the G614 virus had become dominant (Table , illustrated in Figure A and B). , The differences in results between the two types of cohorts are shown in the forest plots (Figure A). The pooled prevalence of olfactory dysfunction in the same ethnicity (South Asians) in regions with D614 predominance was 5.33% (95% confidence interval, CI = 3.52–8.00%), while in regions with G614 predominance, it was 31.79% (95% CI = 23.26–41.76%) (Figure A, C).…”
Section: Resultsmentioning
confidence: 99%
“…Saniasiaya et al (2021) cita que existem três hipóteses para explicar a fisiopatologia da disfunção olfatória decorrente da Covid-19, sendo elas: (1) obstrução mecânica, seguida da inflamação ao redor da fenda olfatória, impedindo que partículas odorantes se liguem aos receptores olfatórios; (2) infecção da célula de suporte que expressa ACE-2; e (3) invasão direta dos neurônios olfatórios pelo vírus, impedindo a transmissão da sinalização olfativa. Para Hajare et al (2021), o zinco sérico pode relacionar-se diretamente à anosmia e à disfunção do paladar, uma vez que serve como fator chave para a atividade da anidrase carbônica, mecanismo funcional presente no muco nasal e na saliva. Concomitante a isso, assim como supracitado, a ACE2, mais uma vez, é referida pelo autor como receptora direta do SARS-CoV-2.…”
Section: Resultsunclassified
“…After 14 days, there was a 63.21% improvement in the sense of taste when compared to taste during the disease period. 25 According to one study from Turkey (155 subjects from a "pandemic hospital" were included in the period from 25.3. to 25.4. 2020, age 18-72 years, average 36.3 ± 8.1 years), 35.4% of the subjects had anosmia and 16.1% ageusia.…”
Section: Covid-19 a N D Olfactory A N D Gustatory Dysfunctionmentioning
confidence: 99%